Optimalisasi Waktu Kerja Karyawan Menggunakan Metode Hungarian (Studi Kasus CV Bintang Jaya) - Wulan Raisa Nabila; Dene Herwanto; Winda Rana Zahra (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
The most common problem in business and industry today is the optimal allocation of production resources, i.e. providing different levels of productivity in different tasks. The challenge of CV Bintang Jaya is how to optimize working hours according to the working hours of its employees. The purpose of this study is to determine the working time of employees in accordance with the work. The research method used is hungarian using the POM-QM application for Windows. Data are collected through observation, interviews, documentation and literature study. From this study, the best results are obtained based on the work. Employee 1 takes 17 minutes to perform the wood cutting operation, employee 2 takes 35 minutes to make a pattern, employee 3 takes 10 minutes to perform the smoothing operation, and employee 4 takes 10 minutes to perform the assembly operation.